2022
DOI: 10.1021/acs.langmuir.2c01250
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Accelerates the Lateral Motion of DPPC Membranes

Abstract: Curcumin, the main ingredient in turmeric, has attracted attention due to its potential anti-inflammatory, anticancer, wound-healing, and antioxidant properties. Though curcumin efficacy is related to its interaction with biomembranes, there are few reports on the effects of curcumin on the lateral motion of lipids, a fundamental process in the cell membrane. Employing the quasielastic neutron scattering technique, we explore the effects of curcumin on the lateral diffusion of the dipalmotylphosphatidylcholine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…This type of motion has been characterized by various models, including ballistic flow-like motion, 43 Fickian diffusion, 44 subdiffusion, 58 and localized diffusion. 59 It is found that Fickian diffusion is valid at least for distances greater than the molecular diameter, [5][6][7]11 which is the case for the length scale accessible by the present QENS experiment. Hence, we have used the Fickian diffusion model, and the scattering law for the lateral motion can be written as 41,42…”
Section: Small-angle Neutron Scattering (Sans)supporting
confidence: 58%
See 3 more Smart Citations
“…This type of motion has been characterized by various models, including ballistic flow-like motion, 43 Fickian diffusion, 44 subdiffusion, 58 and localized diffusion. 59 It is found that Fickian diffusion is valid at least for distances greater than the molecular diameter, [5][6][7]11 which is the case for the length scale accessible by the present QENS experiment. Hence, we have used the Fickian diffusion model, and the scattering law for the lateral motion can be written as 41,42…”
Section: Small-angle Neutron Scattering (Sans)supporting
confidence: 58%
“…This type of motion has been characterized by various models, including ballistic flow-like motion, Fickian diffusion, subdiffusion, and localized diffusion . It is found that Fickian diffusion is valid at least for distances greater than the molecular diameter, , which is the case for the length scale accessible by the present QENS experiment. Hence, we have used the Fickian diffusion model, and the scattering law for the lateral motion can be written as , S lat ( Q , E ) = L lat ( normalΓ lat , E ) = 1 π normalΓ lat false( E / false) 2 + Γ lat 2 where Γ lat is the half-width at half-maxima (HWHM) of the Lorentzian function corresponding to the lateral motion of the lipid molecules.…”
Section: Theoretical Aspectsmentioning
confidence: 58%
See 2 more Smart Citations
“…Vibrational spectroscopy can offer small probes and high temporal resolution. C–H stretching modes of methylene groups were found to be useful to probe lipid conformations in lipids, allowing to discriminate between gauche- and anti-conformations. However, atomic assignment using CH stretching modes is difficult due to vibrational coupling of different methylene groups along the chain. Two-dimensional infrared (2DIR) spectroscopy has emerged as a tool for elucidating molecular interactions and structural dynamics, including those of the lipid bilayers. Molecular motions of a cell membrane, including the motions on an ultrafast scale, are essential for the cell to conduct its biological function.…”
Section: Introductionmentioning
confidence: 99%